le-Hibanot me-ʻevro ha-aḥer shel ha-o,kyanus - Elkin, Rivka (The Jewish press in the Nazi Germani - Texts and research 9, 2021)
Aufbau - the journal of American immigrants from Germany and their immigration and adjustment problems 1938-1941